Bentuk Penyajian Tari Sapu Tangan dalam Acara Malam Barinai Versi Siti Zubaidah pada Masyarakat Pesisir Sibolga - Dwi Irna Hasana Tanjung (Universitas Negeri Medan, 2016)
The research desribed about Sapu Tangan dance (introduce dance) tahat alsocalled as Kapri dance in Malam Barinai ceremony at Sibolga costal society. Tosupport the analyze of the research, the writer especially used the formtheory ofK.Langer. The elemens of the dance are move, accom paniment, the dressing andcostum, the place of perfoemance and equipment, same as the theory of K.Langer,who also used the theory of Jazuli presentation. The proccess to produce the dataof this research has done since January until March 2016. The data of research hascollected by Legwork, the method that lonsist of some aspects: observation,interview theoritical aand documentation. Then the writer analyze by usedkuatitative descriptive method. The result of the research as Sibolga costal soctety,is heterogeneous that consist of come ethnict. The artist of Sibolga has variantperception Sikambang that implementation at Malam Barinai.